Epitaxial HfTe2 Dirac semimetal in the 2D limit - Polychronis Tsipas; Panagiotis Pappas; Evgenia Symeonidou; Sotirios Fragkos; Christina Zacharaki; Evangelia Xenogiannopoulou; Nikitas Siannas; Athanasios Dimoulas (APL Materials, 2021)
One monolayer semimetallic HfTe2 thin films are grown on three substrates with different electronic properties in order to study the substrate effect on the electronic structure of the HfTe2 epilayer. Angle resolved photoelectron spectroscopy measurements indicate that the band features are identical in all three cases, providing evidence that the HfTe2 epilayer does not interact with any of the substrates to form hybridized bands and any band feature originates from the HfTe2 material itself. However, a shift of HfTe2 energy bands is observed among the three cases, which is attributed to substrate electron doping. This paves the way for accessing the Dirac point of HfTe2 Dirac semimetal, which is located about ∼0.2 to 0.3 eV above the Fermi level in the case of suspended HfTe2 in a non-destructive way.